A DFT study on the formation of heterocycles via iodine(iii)-promoted ring expansion reactions. (21st October 2022) - Lussari, Natália; Khan, Ajmir; Pilli, Ronaldo A.; Dos Santos, Alcindo A.; Silva, Luiz F.; Braga, Ataualpa A. C.
Abstract : Combined computational–experimental study to elucidate the mechanism of HTIB-promoted ring expansion reaction of bicyclic heterocycles bearing an exocyclic double bond. Abstract : The ring expansion of bicyclic heterocycles bearing an exocyclic double bond promoted by Koser's reagent [hydroxy(tosyloxy)iodobenzene, HTIB] is a mild, practical, and metal-free methodology to access seven-membered rings containing fused furan, indole, pyrrole, and thiophene heterocycles providing an entry to structurally challenging bioactive natural products as well as pharmaceuticals. Here we describe our DFT results for the reaction conducted in aqueous methanol (95 : 5 v/v). These computational studies involving the microsolvation approach validated the regiochemistry of such kinetically favored rearrangements and helped to explain the faster reaction rate observed in aqueous methanol when compared to aqueous acetonitrile showcasing a fundamental role of protic solvents during the nucleophilic addition step which may support further experimental studies.